"Groupies" and "Jersey Chasers": Male Student‐Athletes' Sexual Relationships and Perceptions of Women. Issue 163 (11th July 2018) - Nelson, Jennifer
Abstract: This chapter explores the concept of "groupies" and "jersey chasers." Hegemonic masculinity and the cultures of entitlement, silence, and protection are used to frame these concepts. Implications are offered for student success, personal development, and for those who work with male athletes.